Pengaruh Kompetensi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan pada PT Pelabuhan Indonesia (Persero) Regional 4 Makassar - Erwin Agus; Jihan Safira Rospitasari Harun Sally; Melisa Yanuar Susilo; Sirajuddin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of competence and work environment on employee job satisfaction at PT Pelabuhan Indonesia (Persero) Regional 4 Makassar. Job satisfaction is a strategic issue because it is closely related to productivity, loyalty, job stability, and the quality of organizational services. This study uses a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to employees as research respondents. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to test the relationship between variables simultaneously. The competency variable is measured through indicators of knowledge, skills, work ability, and professionalism. The work environment variable is measured through physical conditions, work comfort, communication, inter-employee relationships, and organizational support. Meanwhile, job satisfaction is measured based on employee perceptions of work, comfort, rewards, and overall work experience. The results show that competence has a positive and significant effect on employee job satisfaction. The work environment is also proven to have a positive and significant effect on job satisfaction. Simultaneously, competence and the work environment provide a meaningful contribution in explaining variations in employee job satisfaction. These findings emphasize the importance of strengthening individual competencies and creating a conducive work environment as a strategy to increase job satisfaction and sustainable organizational performance.